2019
DOI: 10.1002/anie.201900911
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Ring Cyclodextrins as Chiral Selectors for Enantiomeric Pharmaceuticals

Abstract: Large-ring cyclodextrins (CD) are cyclic glucans composed of 9o rm ore a-1,4-linked glucose units.T hey are minor side products of bacterial glucanotransferases (CGTases,E C2.4.1.19) and have previously been available only in very small amounts for studies of their properties in supramolecular complex formation reactions.W ee ngineered aCGTase to synthesizemainly large-ring CD facilitating their preparation in larger amounts.B yr eversed phase chromatography,w eo btained single CD samples composed of 10 to 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…The α-, β-, and γ-cyclodextrins are widely known, which contain 6, 7, and 8 units respectively. Recently the smallest cyclodextrins were synthetized, containing 3 and 4 glucopyranose units [2], and on the other hand big oligosaccharides with more, than 8 units are also known [1] and applied for complexation [3] or as chiral selectors for enantiomeric pharmaceuticals [4]. Glucopyranose units form a conical cylinder, which has a hydrophobic inner cavity and a hydrophilic outer surface.…”
Section: Introductionmentioning
confidence: 99%
“…The α-, β-, and γ-cyclodextrins are widely known, which contain 6, 7, and 8 units respectively. Recently the smallest cyclodextrins were synthetized, containing 3 and 4 glucopyranose units [2], and on the other hand big oligosaccharides with more, than 8 units are also known [1] and applied for complexation [3] or as chiral selectors for enantiomeric pharmaceuticals [4]. Glucopyranose units form a conical cylinder, which has a hydrophobic inner cavity and a hydrophilic outer surface.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins (CDs) composed of 6, 7 and 8 glucopiranose units α-CD, β-CD, and γ- CD are produced commercially. They form cone-shaped structures with a hydrophobic cavity and an outer hydrophilic area, enabling the reversible binding of hydrophobic molecules in their cavity to form supramolecular host-guest complexes ( Sonnendecker et al, 2019 ). They are used to encapsulate food flavours and aromas, orange aroma by α-cyclodextrin, d -limonene, menthol, and shiitake flavour byβ-CD, and encapsulated aromas are stable during storage ( Fenyvesi & Szente, 2016 ).…”
Section: Molar Mass Effect On Flavour Intensitymentioning
confidence: 99%
“…Large ring CD up to DP 37 has been prepared, and proved non-toxic, but is not produced in a great quantity. Sonnendecker et al (2019) reported that CDs with DP = 10 and 11 were effective for the enantiomeric separation of several enantiomeric pharmaceuticals ( Sonnendecker et al, 2019 ). Although the larger CDs were thought to be unsuitable for enatiomeric discrimination because of the increasing flexibility of larger CD rings, CD10 (CD with DP = 10) to CD12 (CD with DP = 12) were believed to be different from CD6 (α-CD) to CD8 (γ-CD) while still providing sufficient rigidity to form stable complexes.…”
Section: Molar Mass Effect On Flavour Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclodextrins (CDs) containing more than 9 glycose units, referred to as large-ring CDs (LR-CDs), 4 can assume a helical folding arrangement, e.g., the 26-membered CD. [5][6][7][8][9] LR-CDs with 14 units have been shown to adopt a conformation that resembles a concave polygon. 10,11 Large pillar[n]arenes, where n = 8-10, containing up to 10 monomers in their structures, also adopt concave polygon shapes.…”
mentioning
confidence: 99%